The Potential Regulatory Network of Glutamate Metabolic Pathway Disturbance in Chinese Han Withdrawal Methamphetamine Abusers - Peng, Sufang; Su, Hang; Chen, Tianzhen; Li, Xiaotong; Du, Jiang; Jiang, Haifeng; Zhao, Min (Frontiers in Genetics, 2021)
Objects: To explore the long-term influence of methamphetamine abuse on metabolomics character with gas chromatography-mass spectrometry (GS-MS) technology, and the potential regulatory network with bioinformatics method. Methods: 40 withdrawal methamphetamine abusers (WMA) were recruited from Shanghai Gaojing Forced Isolation Detoxification Institute. 40 health controls (HC) were recruited from society. GS-MS technology was used to detect metabolic products in serum. Bioinformatics method was used to build a regulatory network. Q-PCR was used to detect the candidate genes expression, and ELISA was used to detect the regulatory enzymes expression. Results: Four pathways were significantly changed in MA compared to HC: (1) arginine synthesis pathway, (2) alanine, aspartic acid and glutamate metabolic pathway, (3) cysteine and methionine metabolic pathways, and (4) ascorbate and aldarate pathway (enrichment analysis p < 0.05，Impactor factor > 0.2). When focusing on the ‘Alanine, aspartate and glutamate metabolism’ pathway, regulatory network was established and the expression of candidate regulatory genes and enzymes was verified. It was found that the expression of DLG2(Discs large MAGUK scaffold protein 2), PLA2G4 (Phospholipase A2 group IVE), PDE4D (Phosphodiesterase 4D), PDE4B (Phosphodiesterase 4B) and EPHB2 (Ephrin type-B receptor 2) were significantly different between the two groups (p < 0.05), However, after adjusted age and BMI, only DLG2, PLA2G4, EPHB2 still keep the significance (p < 0.05). While the expression of enzymes was not significantly different (p > 0.05). Conclusions: Methamphetamine abuse has a long-term influence in the metabolic process, DLG2, PLA2G4, EPHB2 may regulate the glutamate metabolism pathway.